Plasma Cell Gingivitis Treated with Photobiomodulation, with No Recurrence for a Five-Year Follow-Up. (12th October 2022) - Pulicari, Federica; Pellegrini, Matteo; Pascadopoli, Maurizio; Porrini, Massimo; Kuhn, Elisabetta; Scribante, Andrea; Spadari, Francesco
Abstract : Introduction . Plasma cell gingivitis (PCG) is a chronic inflammatory disease usually affecting the vestibular portion of the gingival mucosa. Clinical presentation is marked by erythematous macules of intense red color, confluent, and delimited from the healthy neighboring mucosa. Generally asymptomatic, the gum lesions sometimes are accompanied by burning sensations and a sense of local tension. Recommended treatment is the use of topical steroids, but with apparent initial healing that is not stable over time. The present case report concerns a patient diagnosed with PCG in November 2017, with a five-year follow-up. This is the first patient with PCG successfully treated with non-surgical periodontal therapies associated with photobiomodulation (PBM). Methods . A 64-year-old male patient had intense erythema and edema on the vestibular side of the gingival mucosa area from 1.5 to 2.5. The patient's symptomatic subjectivity parameters were evaluated through dedicated questionnaires. Erythema and gingival bleeding were also evaluated. Periodontal charting was not pathological, but intense bleeding was noted. Multiple biopsies were performed, and microscopic findings confirmed the clinical hypothesis of PCG. Results . The treatment applied was PBM associated with periodontal therapy. The patient demonstrated a progressive improvement in clinical parameters considered and reported symptoms. During the five-year follow-up, no recurrence of the disease was observed. Conclusions . The combined PBM and periodontal therapies have proved to be sufficiently effective in the control of PCG, showing reduction of the intense inflammatory, erythematous component, and gingival bleeding, and are a valid treatment alternative to topical steroids.